(untitled) (Experimental biology, 2026)
This study investigated the genetic structure of an Auliekol cattle population comprising 308 individuals sampled from the “Timofeev-Agro” farm located in the Auliekol district of the Kostanay region, Kazakhstan, using BovineSNP50 data. After quality control, 22,865 autosomal SNPs were retained for analysis, and the average genotype call rate reached 0.99947. Population structure was assessed using principal component analysis (PCA), ADMIXTURE, and identity-by-descent (IBD)-based genetic similarity analyses. PCA revealed a compact clustering of most samples, indicating the absence of pronounced population stratification, while a limited number of samples showed moderate deviations from the central cluster, reflecting within-population genetic variation. IBD analysis further confirmed the genetic integrity of the population, revealing a dense and continuous genetic similarity network without clear separation into discrete groups. ADMIXTURE analysis performed for K values ranging from 2 to 5 demonstrated the predominance of a single major ancestry component across the population. The presence of additional ancestry components at varying proportions in some individuals did not support the existence of distinct subpopulations. Overall, the concordant results of PCA, ADMIXTURE, and IBD analyses indicate that the Auliekol cattle population is genetically homogeneous, lacks pronounced subpopulation structure, and exhibits a natural level of within-population genetic diversity. These findings suggest that this population represents a stable and reliable genetic resource for further genomic studies and breeding programs.